THE EFFECT OF SALES GROWTH AND LEVERAGE ON FINANCIAL DISTRESS WITH PROFITABILITY AS A MODERATION VARIABLE - Dheo Rimbano; Tri Agriana Sari; Wisdalia Maya Sari; Ade Famalika; Zahra Hermalia Putri (Jurnal Media Ekonomi (JURMEK), 2025)
This study aims to determine and analyze the effect of sales growth and leverage on financial distress with profitability as a moderating variable in a case study of cosmetic companies listed on the Indonesia Stock Exchange from 2014 to 2024. The population in this study consisted of seven companies. The sample was selected using purposive sampling, resulting in a sample of five companies with 11 years of observation, yielding 55 pieces of research data. The method used was panel data regression analysis with the Fixed Effect Model (FEM) approach, and the moderating variable was tested using the Moderated Regression Analysis (MRA) model. Both models were analyzed using the EViews program. The results showed that sales growth and leverage did not have a significant effect on financial distress; profitability was unable to moderate the relationship between sales growth and financial distress, while profitability was able to moderate the relationship between leverage and financial distress.